Pendampingan Penerbitan Nomor Induk Berusaha (NIB) bagi UMKM di Kecamatan Sukodadi Kabupaten Lamongan - Imam Syafi’i; Samsul Arif; Rasio Hepiyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the implementation of assistance for issuing Business Identification Numbers (NIB) for Micro, Small, and Medium Enterprises (MSMEs) in Sukodadi District, Lamongan Regency. This assistance program is a government effort to support MSMEs in obtaining business legality regulated through the Online Single Submission (OSS) system. The method used in this study is a descriptive qualitative approach with data collection techniques through in-depth interviews, field observations, and document studies related to program implementation. The results show that NIB assistance has a positive impact on MSMEs' understanding and awareness of the importance of business legality, which was previously neglected. However, there are several obstacles in its implementation, including limited digital literacy among MSMEs and limited internet access in some areas, which hinder the NIB registration process through the OSS system. Furthermore, although assistance has been provided by local governments and related agencies, it is necessary to increase the frequency and quality of assistance to make the NIB registration process easier and more efficient for MSMEs. Therefore, a more intensive mentoring policy based on technology empowerment is urgently needed to support the sustainability of business legality among MSMEs in Sukodadi District.